The initiative of the Central Bank of Iraq and its impact on some banking activities provided by specialized banks (Journal of Accounting and Financial Studies ( JAFS ), 2022)
Specialized banks provide their banking activities to their customers at interest rates that are determined according to the approved bank policy, which is almost similar to most or most banks. To satisfy the financial desires of customers and at the same time it is a source of the bank's profits, However, these banks have been introduced to new services that they provide with the funds of the Central Bank initiative launched at the beginning of (2016) to address the economic stagnation that befell the country due to the (financial security) crisis that the country faced in 2014. To put forward initiatives amounting to nearly (15) trillion dinars, which were put forward through private commercial and Islamic banks and specialized banks.The research derives its importance from knowing the impact, whether positive or negative, that the Central Bank of Iraq’s initiative leaves on the activities offered by specialized banks. Banking services through the initiative Self-banking services , As the research started from a basic assumption based on the success of the Central Bank of Iraq in its initiatives to support large and residential projects, which amounted to approximately (10 trillion) dinars, positively affecting the operations and activities of specialized banks. During the period (2016-2021).The research has several conclusions, most notably (the unconventional monetary policy was used at a time when there was a financial and security crisis, the Central Bank of Iraq at that time was forced to adopt this policy in order to overcome a crisis that afflicted the country at its time, as the total sums of the initiatives launched by it amounted to approximately ( 15) A trillion, has been pumped into the Iraqi economy during (6) years and continues for the present time, but continuing to grant it without studying may lead to the occurrence of problems and inflationary effects in the economy) And (the increase in the amounts allocated and granted to the real estate and industrial sector compared to the decrease in the amounts allocated and granted to the agricultural sector) and to a set of recommendations, the most important of which is (the Central Bank of Iraq to carry out continuous studies to demonstrate the impact of initiatives on the economy in general and on banks in particular, and to determine the appropriate timing for a smooth and gradual exit from this stage And return to the normal size of the central bank budget , In order to avoid the risk of a possible tightening of financial conditions beyond their supportive level for economic activity, because stopping them suddenly may lead to a shock in the Iraqi economy) as well as (the Central Bank should increase the amounts allocated and granted to the Agricultural Bank to be able to support the agricultural sector, which will contribute to supporting local production and lack of reliance on Imported agricultural products and crops).